(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
هدف البحث إلى تعرّف دور الأهل في إكساب أطفالهم التربية الجنسيّة السليمة، والوقوف على مدى إدراكهم لأهميّة التربية الجنسيّة لأطفالهم، تبعاً لمتغيرات (الجنس، الشهادة العلمية، عدد الأولاد). أجري هذا البحث في ريف محافظة طرطوس، وقد بلغ عدد أفراد عينة البحث (240) أباً وأماً ممن لديهم أطفال في الحلقة الأولى من مرحلة التعليم الأساسي، ولتحقيق هدف البحث تمّ توجيه استبانة مؤلفة من (27) عبارة، وتم التحقق من صدقها وثباتها بتوزيعها على عينة استطلاعية بلغت (26) أباً وأماً، وقد بلغ معامل كرونباخ ألفا(0.801). وقد أظهرت نتائج البحث وجود وعي من الأهل آباءً وأمهات لأهميّة التربية الجنسيّة للأطفال بدرجة متوسطة، وبينت النتائج أن الفروق التي ظهرت بين متوسط إجابات أفراد عينة البحث هي فروق غير دالة وغير جوهرية حول إدراكهم لكيفيّة قيامهم بالتربية الجنسيّة للأطفال تبعاً لمتغيري (الجنس، عدد الأولاد)، ووجود فروق دالة وجوهرية تبعاً لمتغير الشهادة، لصالح حملة الشهادة الجامعية، أوصى البحث بضرورة توعية الأهل بأهميّة التربية الجنسية وضرورتها، والتفكير بطريقة مناسبة لإدخال التربية الجنسيّة للمناهج المدرسيّة منذ مراحل مبكرة. The research aims at identifying the role of parents in acquainting their children with safe sexual education to evaluate and appreciate how far they are aware of the significance of sexual education in their children according to (sex, academic diploma, and number of children) variables. The research has been conducted in Tartous Rural province. The number of research sample 240 fathers and mothers whose children belong to the first Basic Education stage. To achieve the objective of the research a questionnaire has been included (27) items. The validity of the questionnaire has been verified and distributed to a sample exploratory of (26). The Cronbach Alfa amounted to 0.8.The results showed that parents are really aware, on average, of the significance of the sexual education for children. Also showed that differences by average answers but not fundamentals with respect to their awareness of how they should provide their children with sexual education according the sex and number of children. Also according to the diploma variation. The research recommended that parents are necessary to be made aware of the significance of sexual education and they should also consider a proper way for introducing sexual education into school curricula at early stages.